An analysis of the issues and prospects facing SriLankan Airlines and its embedded partnership with Sri Lankan tourism - Nagahawatte, L.; O'Connell, John F. (IP Publishing, 2016)
The long civil war, which ended in May 2009, poor economic performance and weak travel demand for Sri Lanka all coalesced in hindering the tourism industry. Consequently its aviation industry, which is dominated by the national carrier SriLankan Airlines, faced growing and difficult challenges. However, since 2009 the country has witnessed a boom in tourism, while an unprofitable SriLankan Airlines changed its financial and strategic circumstances by becoming a member of the Oneworld alliance in mid-2014, driven by its regional geography and proximity to India which had strict bilateral traffic rights for international incumbents from the UK and the UAE. This study analyses tourism, economic and passenger data combined with results from a passenger survey and expert interviews in order to identify the critical issues and future prospects of aviation and tourism in Sri Lanka. The authors conclude that its ageing long-haul fleet, together with an inferior economy-class product along with high fuel prices, capacity constraints and poor management practices are the major issues faced by SriLankan Airlines. On the tourism side, uncompetitive hotel rates, unnecessarily high government taxes, visa charges and the lack of international promotion were seen as the principle drawbacks. A survey at Colombo airport revealed that fare is the principle rhetoric for passengers taking SriLankan Airlines but when they want a wider range of additional and superior attributes they choose foreign carriers.
Keywords: Sri Lanka; SriLankan Airlines; Tourism; Oneworld